Making connections for children and teachers: using classroom-based implementation supports for teaching Pyramid Model practices in Head Start programs - Bulotsky-Shearer, Rebecca J.; Ehrenreich-May, Jill; Morris, Chelsea T.; Mullins, Casey; Lerner, Bella S.; Howe, Elizabeth; Bailey, Jhonelle; Gruen, Rinatte L.; Gonzalez, Angelica C. (Frontiers in Education, 2025)
IntroductionIn partnership with an urban school district Head Start program, we created a set of intervention supports that built upon the strengths of the district program services already in place.MethodsWe conducted a randomized control trial to test the use of natural helpers (teachers, special education coaches, and curriculum specialists) participating in practice-based coaching and monthly communities of practice, to augment a districtwide universal social-emotional program, The Pyramid Model for Promoting Social and Emotional Competence in Infants and Young Children. Participants included 53 preschool teachers and 519 preschool children, across 26 classrooms, and 9 schools in a high poverty area of the district. Teachers were randomized to a waitlist control or intervention condition. Intervention teachers participated in practice-based coaching and monthly communities of practice over the course of two years.ResultsSignificant effects were found on participating intervention teachers’ observed increased implementation of positive social-emotional practices in the classroom, decreases in red flags (observed teaching behaviors counter to the Pyramid Model), and increased teacher reports of self-efficacy in the intervention group, compared to control teachers. No significant impacts on child classroom behavior problems, self-regulation, or approaches to learning skills were found for children enrolled in intervention classrooms, compared to children in the control classrooms.DiscussionFuture directions for research and implications for practice are discussed.